(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dyslexia is a learning disorder that involves difficulty in reading due to problems identifying speech sounds and learning how they relate to letters and words (decoding). It is identified that 5% to 17% of the world population are dyslexics. They tend to possess serious problems like identifying speech sounds and learning how they relate to letters and words, processing graphic symbols. They find it hard to spell correctly, read and write fluently compared to other children of their age. To overcome the stumbling blocks in learning for dyslexics, we develop a web application, that concentrates on helping dyslexic children to learn, read and write alphabets. This paper briefs upon employing cumulative and adaptive techniques for learning and evaluate the dyslexic students based on 3 criterions namely- visual, phonology and memory. The three modules are as follows- (i) Catapult (ii) Unleash ravel (iii) Cumulative digest. Within the Catapult module, the child is taught to read and write an alphabet by a video. It are often played until the child is confident. Next within the Unleash ravel module, three tests are conducted to instill various micro-skills. Firstly, the child is asked to write down the alphabet that’s instructed on a piece of paper. It’s captured and evaluated using OCR. Secondly, the kid is asked to spell the alphabet that is displayed on the screen and record it. Eventually, the child is asked to sequentially identify the alphabet in question from a paragraph. It’s done to enhance the visual tracking, visual discrimination skills of the child . When the child moves to further chapters, the previous lessons are cumulatively added to the Unleash ravel to enhance memory. The Cumulative Digest gives the report of the child’s performance in three categories analyzing the micro-skills using machine learning. They are Visual, Phonology and Memory. A threshold is set for each test and if the kid score below the edge then tests are made to be adaptive in order that the child faces more exercises within the part he/she is under performing at. Thus, the TPTL application helps dyslexics to learn, test and analyze their skills which will improve their letter recognition, visual tracking, visual discrimination, visual memory, auditory memory and auditory discrimination.